Citizenship Needs in the Daily Activities of Elementary Madrasah Students - Jariyah, Waode Sri Nur; Harahap, Fitri Khoiroh Sayidah (Cendekiawan : Jurnal Pendidikan dan Studi Keislaman, 2023)
This study aims to identify and analyze the citizenship needs reflected in the daily activities of madrasah ibtidaiyah students, as well as the role of these activities in the formation of students' citizenship character. This research uses a qualitative approach with a case study method involving observation, interviews, and documentation as data collection techniques. The research informants consisted of teachers, students, and principals in madrasah ibtidaiyah in Kendari City. The results show that daily activities such as the implementation of class pickets, flag ceremonies, religious activities, and social interactions between students serve as a means to instill citizenship values, including responsibility, cooperation, justice, and social care. Through engagement in these activities, students not only acquire knowledge of their rights and obligations as citizens, but also develop social skills and attitudes that support their role in society. This research suggests that schools should further integrate citizenship activities in students' daily activities to enhance civic learning that is more applicable and contextual, by strengthening the role of teachers in facilitating the internalization of these values.